184k views
4 votes
3(-2a-4)+3a what would this be i have so many questions today to ask y'all

User Artnikpro
by
5.0k points

2 Answers

2 votes

Answer:

-3(a+4)

Explanation:

User Billias
by
4.7k points
5 votes

Answer:


- 3(a + 4)

Solution,


3( - 2a - 4) + 3a \\ = 3 * ( - 2a) - 3 * 4 + 3a \\ = - 6a - 12 + 3a \\ = - 6a + 3a - 12 \\ = - 3a - 12 \\ = - 3(a + 4)

Hope this helps...

Good luck on your assignment...

User Ben Sewards
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.